The Impact Applying of Fair Value Accounting on the Financial Statements Information Indicators in Jordanian Commercial Banks - Hamdan, Mohammad; AL-Khawaldeh, Fatima (The Arab Journal of Administration, 2021)
This study aims to demonstrate the impact of application fair value accounting on the significance financial statements information at Jordanian Commercial Banks, and define the impact of reporting based on fair value, which discloses financial data to its users, the impact of these data on the income statements and balance sheet. To achieve the goals of the study, the researchers depended on secondary sources represented in books, bank’s published reports, references, theoretical and experimental researches, researches and periodicals. On the other hand, primary source by conducting a scientific questionnaire, the community of the study consisted of the financial statements’ preparers. The researchers have distributed, only (113) questionnaires were analyzed statistically, representing (30%) of the total distributed questionnaires. The results of the study showed that there is an impact of fair value accounting application on the financial statements information significance at Jordanian Commercial Banks, the study found that published financial statements of fair value is useful in giving accounting information of high level of creditability and reliability, and help in discovering financial faults, based on that. The study recommended the necessity of paying attention, developing, supporting and establishing fair value accounting by the specialized authorities, and to instruct the features and advantages of the fair value, to make brochures and conduct conferences and seminars to make aware of fair value accounting.